Mapping Minds in Chemistry: Implementing the Flow Map Method within the 8E Learning Cycle to Uncover Students’ Cognitive Structures - Elma Suryani; Achmad Ridwan; Rizky Sulistyowati; Edith Allanas; Sarina Hanifah; Fazila Windy Febriani; Ahmad Hafizh; Musyahadah Rodiatam Mardiah (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2026)
Understanding students’ cognitive structure is essential for improving conceptual learning in science, particularly in challenging topics such as the rate of reactions. However, many students struggle with fragmented knowledge and misconceptions in this area. This study investigates how the 8E Learning Cycle model supports the development of students’ cognitive structure, analyzed through the flow map method. The participants were 33 Senior high school students, and a qualitative approach was employed using multiple data sources (flow maps, worksheets, interviews, journals, observations, and comprehension tests). Cognitive structure was examined based on Tsai’s six variables: extent, richness, integration, misconceptions, information retrieval rate, and flexibility. Results indicated that at the beginning of instruction, students’ average scores on cognitive structure variables were low, while misconceptions were frequent. After engaging in the 8E Learning Cycle, students demonstrated notable improvement across all variables, accompanied by a marked reduction in misconceptions. This study provides empirical evidence that the 8E Learning Cycle model effectively strengthens students’ cognitive structures in science learning, offering a practical framework for addressing conceptual difficulties in reaction rate topics